Lens design basics : optical design problem-solving in theory and practice - Gerhard, Christoph, 1977- (IOP series in emerging technologies in optics and photonics., 2020)
This book gives a comprehensive overview on the principles of optical imaging. The first seven chapters provide an extensive summary of optical design, as well as the mechanisms and interrelations leading to the formation of aberrations and the accompanying decrease in imaging performance. Aside from the fundamentals of optics and imaging models, topics covered include calculations of simple optical components and systems, characterisation and quantification of aberrations and defects in optical systems, and optimisation of imaging performance. The second part focuses on problem-based learning via multiple exercises and case examples derived from the first seven chapters. It is an ideal guide for optics and photonics students. Part of IOP Series in Emerging Technologies in Optics and Photonics.